The East-West German gap in revenue productivity: Just a tale of output prices? - Matthias Mertens; Steffen Müller (Halle Institute for Economic Research (IWH), 2020)
East German manufacturers' revenue productivity (value-added per worker) is some 8 (25) percent below West German levels, even three decades after German unification. Using firm-product-level data containing information on product quantities and prices, we analyse the role of product specialisation and reject the prominent 'extended work bench hypothesis', stating a specialisation of Eastern firms in the intermediate input production as explanation for these sustained productivity differences. We decompose the East's revenue productivity disadvantage into Eastern firms selling at lower prices and producing more physical output for given amounts of inputs within ten-digit product industries. This suggests that Eastern firms specialise vertically in simpler product varieties generating less consumer value but being manufactured with less or cheaper inputs. Vertical specialisation, however, does not explain the productivity gap as Eastern firms are physically less productive for given product prices, implying a genuine physical productivity disadvantage of Eastern compared to Western firms.
urn:nbn:de:gbv:3:2-124550
Keywords: D24; L2; L11; O47; 330; German unification; regional productivity gap; physical productivity; product prices; product specialisation